A humanized mouse model identifies key amino acids for low immunogenicity of H7N9 vaccines - Wada, Yamato; Nithichanon, Arnone; Nobusawa, Eri; Moise, Leonard; Martin, William D.; Yamamoto, Norio; Terahara, Kazutaka; Hagiwara, Haruhisa; Odagiri, Takato; Tashiro, Masato; Lertmemongkolchai, Ganjana; Takeyama, Haruko; et al. (Scientific reports, 2017)
Influenza vaccines of H7N9 subtype are consistently less immunogenic in humans than vaccines developed for other subtypes. Although prior immunoinformatic analysis identified T-cell epitopes in H7 hemagglutinin (HA) which potentially enhance regulatory T cell response due to conservation with the human genome, the links between the T-cell epitopes and low immunogenicity of H7 HA remains unknown due to the lack of animal models reproducing the response observed in humans. Here, we utilized a humanized mouse model to recapitulate the low immunogenicity of H7 HA. Our analysis demonstrated that modification of a single H7 epitope by changing 3 amino acids so that it is homologous with a known H3 immunogenic epitope sequence significantly improved the immunogenicity of the H7 HA in the humanized mouse model, leading to a greater than 4-fold increase in HA-binding IgG responses. Thus, we provide experimental evidence for the important contribution of this H7-specific T cell epitope in determining the immunogenicity of an influenza vaccine. Furthermore, this study delineates strategies that can be used for screening and selecting vaccine strains using immunoinformatics tools and a humanized mouse model.